2016
DOI: 10.1007/s10877-016-9849-1
|View full text |Cite
|
Sign up to set email alerts
|

Precision diagnosis: a view of the clinical decision support systems (CDSS) landscape through the lens of critical care

Abstract: Improving diagnosis and treatment depends on clinical monitoring and computing. Clinical decision support systems (CDSS) have been in existence for over 50 years. While the literature points to positive impacts on quality and patient safety, outcomes, and the avoidance of medical errors, technical and regulatory challenges continue to retard their rate of integration into clinical care processes and thus delay the refinement of diagnoses towards personalized care. We conducted a systematic review of pertinent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 76 publications
4
58
0
1
Order By: Relevance
“…Implementation of CDSSs has demonstrated increased efficiency, reduced medical errors, and improved outcomes, but they continue to fall short of their full potential [2-9]. We believe this key shortcoming may partly be due to the lack of physician acceptance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of CDSSs has demonstrated increased efficiency, reduced medical errors, and improved outcomes, but they continue to fall short of their full potential [2-9]. We believe this key shortcoming may partly be due to the lack of physician acceptance.…”
Section: Resultsmentioning
confidence: 99%
“…A CDSS provides alerts, reminders, prescribing recommendations, therapeutic guidelines, image interpretation, and diagnostic assistance. Although studies have shown that CDSSs reduce medical errors and improve outcomes, they also demonstrate that CDSSs fall short of their full potential [2-9]. Research has attempted to narrow in on the cause of this shortfall.…”
Section: Introductionmentioning
confidence: 99%
“…While it is recognized that developing and deploying CDSSs can be very beneficial in contexts that require complex decision-making, such as chronic disease management, their use in routine clinical practice is currently still limited (Belard et al, 2016). Possible causes are related to poor user interfaces, lacking integration with EHRs, and limited analytics capabilities that do not allow data-driven reasoning.…”
Section: Research Informs Care-data Driven Decision Makingmentioning
confidence: 99%
“…In addition, it provides conclusive and objective evidence of small molecular alterations within the tissue that could be related to the early stages of the disease not detectable with standard optical microscopy. While such statistical analysis usually provides excellent results with accuracy varying between 85% and 98%, most physicians are reluctant to rely solely on computer made diagnosis without any visual proofs available for their assessment [16,17]. Improvements of optical systems have been made in order to overcome the limitations of the spatial resolution, signal-tonoise ratio and, to some extent, measurement time [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%